Característica Fitoquímica, análise físico química e atividade adsortiva e alelopática do extrato dos frutos de buriti (Mauritia flexuosa L. f.) - Seixas, Paloma Lima (Brasil, 2025)
Dyes are environmental pollutants recognized as global problems that require intelligent alternatives for their removal. Among the main dyes used in the market, Tartrazine Yellow stands out, as it can cause several damages to the environment. The development of bioadsorbents is essential for sustainability and control of invasive plants. One of the botanical species that is a candidate for the development of bioadsorbents is Mauritia flexuosa L., known as buriti. This article aimed to evaluate: Phytochemical Profile, Physicochemical Analysis and adsorptive and allelopathic activities of the aqueous extract of the fruits of Mauritia flexuosa L. The substrate of Mauritia flexuosa L. was purchased from a local store in the city of Itacoatiara, taken to Itacoatiara, dried in an oven and ground in a mil knives. The bioadsorbent was obtained through the acid route. The following were evaluated: Zero Charge Potential, Bohem Titration, Best Mass, Scanning Electron Microscopy, X-ray Diffraction. The phytochemical profile was determined through chromatic reactions according to the methodology described by Matos, 2009. The in vitro allelopathic assay was conducted in a germination chamber, at a temperature of 25 °C and a photoperiod of 12 hours, using different concentrations of the aqueous extract 0.1 and 1%. Twenty tomato seeds were used to evaluate the following variables: germination percentage, average germination time, germination speed, germination speed index and average root length. The data obtained were statistically analyzed using the SISVAR software. The zero charge potential presented a value between pH 1 and 4. The Bohem titration presented results for chromenes, retomes and pyrones. The best mass ranged from 0.1 mg to 2.0 g of buriti material. SEM analysis showed values of 10 µm. XRD analysis was stable. The phytochemical profile showed: flavonoids, saponins and tannins. The aqueous extract of Mauritia flexuosa L. f showed allelopathic activity against tomato seeds; future studies are needed to investigate the mechanism of action of the components of the aqueous extract of Mauritia flexuosa L f. and their allelopathic activity.